Downregulation of RORα by alcohol promotes TGFβ and α-SMA expression in mouse lung fibroblasts - Fan, Xian; Tao, Hui; Kang, Bum-Yong; Diaz, Nicolas; Baba, Kenkichi; Tosini, Gianluca; Guo, Justin; Yeligar, Samantha M.; Sueblinvong, Viranuj (Frontiers in Medicine, 2026)
IntroductionChronic ethanol exposure increases susceptibility to fibroproliferative maladaptive repair following acute lung injury. Ethanol disrupts molecular circadian rhythms in multiple organs, contributing to liver steatosis and renal fibrosis. Because circadian disruption is linked to TGFβ activation and tissue fibrosis, we hypothesized that ethanol alters lung circadian signaling and promotes profibrotic responses in lung fibroblasts through modulation of TGFβ and α-SMA expression.MethodsLung slices from PER2-luciferase reporter mice fed with 20% (v/v) ethanol in drinking water for 8 weeks or only water (control) for 8 weeks were analyzed for real-time bioluminescent PER2 rhythms over 7 days. Lungs from control and ethanol-fed C57BL/6J mice were collected every 4 h over 24 h to assess rhythmicity of selected core clock genes and selected profibrotic markers mRNA expression. Primary murine lung fibroblasts (PLF) were treated with ethanol and evaluated for circadian gene and protein expression. RORα function was interrogated using siRNA knockdown and pharmacological agonist/inverse agonist, followed by analysis of TGFβ, α-SMA, and fibronectin protein levels.ResultsChronic ethanol ingestion lengthened the circadian period by ~2 h (p < 0.05) and induced a ~7% phase shift in PER2 rhythms in lung slices. Ethanol altered oscillatory patterns of core clock genes (Bmal1, Clock, Rorα, Rev-erbα) and profibrotic markers (Tgfβ, α-SMA, Fn1) in mouse lungs. In vitro, ethanol suppressed BMAL1 and RORα expression in PLF. Activation of RORα with agonist SR1078 reversed ethanol-induced TGFβ and α-SMA upregulation, whereas RORα reverse agonist (SR3335) mimicked ethanol’s effects. Lastly, the silencing of RORα gene expression significantly induced TGFβ and α-SMA, with a trend toward an increase in Fn1.ConclusionEthanol disrupts circadian signaling and enhances profibrotic gene expression in lung fibroblasts, partly through suppression of RORα. RORα activation mitigates these effects, identifying RORα as a potential therapeutic target for ethanol-related maladaptive lung repair.